2015
DOI: 10.1186/s12958-015-0079-z
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-like factor 12 is a novel negative regulator of forkhead box O1 expression: a potential role in impaired decidualization

Abstract: BackgroundDecidualization is a prerequisite for successful implantation and the establishment of pregnancy. Krüppel-like factor 12 (KLF12) is a negative regulator of endometrial decidualization in vitro. We investigated whether KLF12 was associated with impaired decidualization under conditions of repeated implantation failure (RIF).MethodsUterine tissues were collected from a mouse model of early pregnancy and artificial decidualization for immunohistochemistry, Western blot and real-time PCR analysis. Report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 50 publications
3
21
0
Order By: Relevance
“…Interestingly, we have found the 9aaTAD activation domain in Crassostrea gigas, KLF1 ortholog (9aaTAD sequence ELL DYD FIL, gene ID; EKC39171), which closely resembles the first identified 9aaTAD in activator Oaf1 (9aaTAD sequence DLF DYD FLF) (12). Surprisingly, the 9aaTAD activation domains of KLF3 and KLF8 did not activate transcription, which correlated with their repressor function reported previously (52,(81)(82)(83)(84). The accumulation of valines has been shown here again to be associated with the 9aaTAD deactivation (Figures 7).…”
Section: Klf Homology With the Sp Family Revealed Their Activation Dosupporting
confidence: 76%
“…Interestingly, we have found the 9aaTAD activation domain in Crassostrea gigas, KLF1 ortholog (9aaTAD sequence ELL DYD FIL, gene ID; EKC39171), which closely resembles the first identified 9aaTAD in activator Oaf1 (9aaTAD sequence DLF DYD FLF) (12). Surprisingly, the 9aaTAD activation domains of KLF3 and KLF8 did not activate transcription, which correlated with their repressor function reported previously (52,(81)(82)(83)(84). The accumulation of valines has been shown here again to be associated with the 9aaTAD deactivation (Figures 7).…”
Section: Klf Homology With the Sp Family Revealed Their Activation Dosupporting
confidence: 76%
“…Furthermore, LIF is considered to be a direct downstream target gene of ATF3 23 . We have previously demonstrated that Krüppel-like factor 12 (KLF12) is expressed in the glandular epithelium (GE) and stromal cells of secretory-phase endometrial tissue and that KLF12 negatively regulates endometrial decidualization through the transcriptional repression of target genes both in vitro and in vivo 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Several key factors, such as FOXO1A, Krüppel-like factor 12 (KLF12) and orphan nuclear receptor Nur77, have been implicated in regulation of the decidualization process [ 15 17 ]. We have previously demonstrated that KLF12, a progestogen target gene, is expressed in the glandular epithelium (GE) and in stromal cells of secretory phase endometrial tissue and that it negatively regulates endometrial decidualization through the transcriptional repression of target genes both in vitro and in vivo [ 18 ]. This study has revealed that the excessive expression of KLF12 and decreased expression of Nur77 in the endometrium of RIF patients.…”
Section: Introductionmentioning
confidence: 99%